Association Between Visceral Fat and Brain Cortical Thickness in the Elderly: A Neuroimaging Study - Cho, Jaelim; Seo, Seongho; Kim, Woo-Ram; Kim, Changsoo; Noh, Young (Frontiers in Aging Neuroscience, 2021)
Background Despite emerging evidence suggesting that visceral fat may play a major role in obesity-induced neurodegeneration, little evidence exists on the association between visceral fat and brain cortical thickness in the elderly. Purpose We aimed to examine the association between abdominal fat and brain cortical thickness in a Korean elderly population. Methods This cross-sectional study included elderly individuals without dementia (n = 316). Areas of visceral fat and subcutaneous fat (cm2) were estimated from computed tomography scans. Regional cortical thicknesses (mm) were obtained by analyzing brain magnetic resonance images. Given the inverted U-shaped relationship between visceral fat area and global cortical thickness (examined using a generalized additive model), visceral fat area was categorized into quintiles, with the middle quintile being the reference group. A generalized linear model was built to explore brain regions associated with visceral fat. The same approach was used for subcutaneous fat. Results The mean (standard deviation) age was 67.6 (5.0) years. The highest quintile (vs. the middle quintile) group of visceral fat area had reduced cortical thicknesses in the global [β = –0.04 mm, standard error (SE) = 0.02 mm, p = 0.004], parietal (β = –0.04 mm, SE = 0.02 mm, p = 0.01), temporal (β = –0.05 mm, SE = 0.02 mm, p = 0.002), cingulate (β = –0.06 mm, SE = 0.02 mm, p = 0.01), and insula lobes (β = –0.06 mm, SE = 0.03 mm, p = 0.02). None of the regional cortical thicknesses significantly differed between the highest and the middle quintile groups of subcutaneous fat area. Conclusion The findings suggest that a high level of visceral fat, but not subcutaneous fat, is associated with a reduced cortical thickness in the elderly.